Pengaruh Kualitas Produk, Desain Produk, dan Brand Image Terhadap Kepuasan Pelanggan Kniel Sports Indonesia - Rosita Dewi Permata Sari; Sultan Bhagaskara; Mahmudah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify the effect of product quality, product design, and brand image on customer satisfaction of Kniel Sports Indonesia. A quantitative approach was used with a survey method, and data were collected through questionnaires from 100 respondents. Data analysis utilized multiple linear regression to test the influence of product quality, product design, and brand image on customer satisfaction. The results of the study demonstrate that these three variables simultaneously affect customer satisfaction. Meanwhile, partially, product quality and product design influence customer satisfaction, whereas brand image does not affect customer satisfaction. These findings imply that Kniel Sports Indonesia needs to focus on strengthening the brand image while maintaining product quality and design innovation to enhance customer satisfaction and competitiveness in both domestic and international markets.